ANALISIS EKONOMI PROGRAM KAWASAN INDUSTRI AGRO TERPADU (KIAT) PROVINSI GORONTALO - Theodora M Katiandagho (Sam Ratulangi University, 2011)
This research has been conducted in the Integrated Agro Industrial Area (TIP) Province of Gorontalo in November 2010 using the data and using linear programming models. The research aims to find the product combination of corn chips, nuts disco, peanuts eggs should be produced to achieve maximum profit, find out how much the maximum advantage can be achieved by TIPS, and TIPS determine the pattern of production, it is optimal or not. The results showed that the combination product should be produced (packaging / wrappers) sequentially from X1 to X13 are 2545, 314, 76.130, 344, 509, 331, 172, 7, 311, 180, 854, 7. The combination product is a combination of products that can provide maximum benefit. The maximum profit that can be achieved by following the TIP with the combination product that is equal to Rp8.770.206. This advantage is greater than the actual clappers TIPS. TIPS production pattern is not optimal, because for some products there is still a considerable difference between the optimal production and actual production in which the optimal production gives better results (large), and also there is no actual product produced equal to optimal production